PENGEMBANGAN E-MODUL BERMUATAN PROFIL PELAJAR PANCASILA PADA MATA PELAJARAN MATEMATIKA UNTUK KELAS 5 DI SD N 1 PANGENREJO - Efa Yunita Setiyaningrum; Muflikhul Khaq; Nurhidayati (LPPM STKIP Bina Bangsa Meulaboh, 2024)
This research aims to: 1) Produce an E-Module development product containing the profile of Pancasila students in mathematics subjects for class 5 of SD N 1 Pangenrejo in accordance with research and development procedures. 2) Knowing the feasibility of developing an E-Module containing the profile of Pancasila students in mathematics for class 5 of SD N 1 Pangenrejo. The type of research used is Research and Development using the Borg and Gal model with 10 steps, namely Research and Information collection , Planning, Develop Preliminary form of Product, Prelimiary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision, Operational Field Testing, Final Product Revision, Desimination and Implementation. The research subjects were 23 class V students at SD N 1 Pangenrejo. Data collection used observation techniques, interviews and student response questionnaires. The development of an E-Module product containing the profile of Pancasila students in mathematics for class 5 at SD N 1 Pangenrejo has been declared feasible with an average score of 3.57 in the